Public Perception of Service Quality at Sentosa Baru Medan Health Center - Siahaan, Jeconiah Firman Alvaro; Rangkuti, Zoraya Alfathin (Asian Journal of Applied Education (AJAE), 2025)
This study looks at the public's perception of the quality of services at the Sentosa Baru Medan Health Center based on the concept of Bimo Walgito's perception and Parasuraman's service quality. Service quality is measured through five main dimensions. The research method used a quantitative survey with a Likert scale questionnaire and descriptive analysis. The results of the study show that in the Responsiveness dimension, indicators related to accuracy and speed of service still receive many negative responses. As many as 33% of respondents strongly disagree with the speed of service, while 35% disagree with the timeliness of service. Overall, the public's perception of service responsiveness still needs to be improved to match their expectations.